PEMBELAJARAN BERBASIS PENDIDIKAN KARAKTER BERBAHAN AJAR PUISI DENGAN TEKNIK PEMBACAAN HEURISTIK-HERMENEUTIK - Suyitno, Suyitno; Andayani, Andayani; Eko, Nugraheni (LITERA, 2015)
Abstract This study aims to describe teachers’ understanding of: (a) a model of charactereducation- based learning using poems as learning materials, (b) the heuristic-hermeneutic reading technique in poetry learning, and (c) problems of character education using poems as learning materials supported by teachers’ critical attitudes and autonomous participation through the application of the heuristic-hermeneutic reading technique. The study employed the qualitative descriptive technique and was a preliminary study as the first step of model development. The data sources were documents and events involving teachers and students at junior high schools in Karanganyar Regency. The results of the study are as follows. First, there is a gap between the phenomena expected by the poetry learning using the heuristic-hermeunetic reading technique and the actual heuristic-hermeunetic reading technique in the field. Second, the gap is attributable to several factors, namely: (a) the initial competence in poetry learning, (b) poetry learning objective setting, (c) poetry learning implementation, (d) poetry learning methods and strategies, (e) poetry learning media, and (f) poetry learning evaluation.